Analysis of the Islamic Broadcasting Communication Strategy of the Tourism and Culture Office of Langkat Regency in the Development of Tangkahan Nature Tourism - Amalia Andari; Syukur Kholil (STAI Publisistik Thawalib Jakarta, 2025)
Indonesia possesses abundant natural and cultural resources supporting sustainable tourism development, including Tangkahan ecotourism and Halal tourism, which require an integrated communication strategy and community participation. This study examines the implementation of the communication strategy by the Langkat Tourism Office through the theories of Communication Strategy and Integrated Marketing Communications (IMC) to enhance the attractiveness of Tangkahan and raise public awareness of sustainable tourism. This research employs a qualitative case study method with data collection techniques including interviews, observations, and documentation, analyzed through data condensation, data presentation, and conclusion drawing. The data validity is tested using source and technique triangulation. The results indicate that the communication strategy in developing Tangkahan tourism applies the 4A 1P approach, digital promotion, service improvement, and environmental education to strengthen the destination’s competitiveness and support sustainable tourism. The natural beauty, interaction with elephants, and the use of social media are major strengths. However, challenges such as difficult access, geographical conditions, and weather present obstacles, necessitating adaptive, community-based strategies. Positive impacts of this ecotourism include increased community income, job creation, and growing awareness of cultural and environmental preservation. Community involvement in interactions with tourists also reinforces local identity and fosters inclusive and sustainable tourism development. In conclusion, the integrated Islamic communication strategy has successfully developed ecotourism, enhanced the economy, preserved culture, and encouraged community participation in sustainable tourism development.